UNIVQUAKE: juego serio de realidad virtual sobre terremotos en escenarios universitarios - Herrera Solis, Sebastian (2025)
Conventional earthquake drills often fail to provide safe, realistic, and repeatable training for procedural knowledge. This limitation is particularly critical in high-density settings, such as university environments, where it is vital to be prepared in the event of such disasters. Virtual reality (VR) combined with serious games (SGs) provides an opportunity for users to experience and practice responses to such events within a controlled environment. This research describes the design, development, and validation of VR-based SG for earthquake preparedness. The primary objective was to assess the effectiveness of the SG in improving university students’ knowledge of the measures to be taken in the event of earthquakes. The secondary objective was to analyze the correlation between the level of presence experienced in the SG and the knowledge gain. A pre-post study was conducted using a questionnaire validated by expert judgment to measure knowledge acquisition. The results demonstrated a statistically significant increase in participants’ average knowledge scores after using the VR-based SG. Additionally, a noteworthy finding was that no direct correlation could be confirmed between the level of presence reported by the participants and the knowledge they acquired. This research concludes that VR-based SG are an effective technological tool for improving procedural knowledge in earthquake preparedness in university settings, even when subjective presence is not a significant factor in the learning process.